The role of multi-stakeholder collaboration in advancing msmes and creative economy: insights from Gorontalo’s pentahelix policy model - Rachman, Ellys; Thalib, Tety (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
This research employs a mixed-methods approach with an explanatory sequential design. Data were collected from 30 stakeholders representing five Pentahelix actors through structured questionnaires and in-depth interviews. The study focuses on three key variables: Government Role, Community Role, and Academic Role as independent variables, with Implementation Effectiveness as the dependent variable. Data analysis utilized multiple regression analysis and thematic analysis for qualitative data. Statistical analysis revealed that all three stakeholder roles significantly influence implementation effectiveness (R² = 0.699, F = 24.758, p < 0.001). Community Role demonstrated the strongest influence (β = 0.521, p < 0.001), followed by Government Role (β = 0.387, p = 0.001) and Academic Role (β = 0.294, p = 0.003). Qualitative findings identified key success factors including active community participation, government responsiveness, and academia-industry partnerships, while highlighting challenges in bureaucratic coordination, budget adequacy, and technology transfer. The Pentahelix collaborative governance model proves effective for MSME policy implementation, with community engagement serving as the primary driver. However, successful implementation requires addressing structural barriers including bureaucratic inefficiencies, limited financial resources, and weak inter-sectoral coordination. The study contributes to collaborative governance theory and provides practical insights for policy makers in developing regions.